Food gardens, environmental lesson planning and active learning in the life orientation learning area - foundation phase: a case study at Lungelolethu Lower and Higher Primary School - Ncula, Ntombizandile Shirley (Rhodes University, Faculty of Education, Department of Education, 2007)
This study was conducted at Lungelolethu Lower/Higher Primary School in Keiskammahoek at a time when I was struggling to understand and implement the new South African curriculum policy, particularly in the Foundation Phase Life Skills Learning Programme. The research focused on my developing an understanding of key Learning Outcomes and linking them with the National Curriculum Statement principle of social justice, human rights, a healthy environment and inclusivity. During this time I was the key 4-H Programme educator in my school, responsible for school food garden activities. I used the school food garden for this study to explore the opportunities the garden might provide to develop the new curriculum using active learning approaches to teaching and learning; as well as to respond to environmental issues such as poverty. This research was an interpretive case study which supported my reflections within a practical action research framework. This framework suited my intention to change my classroom practice. I undertook three action research cycles with the first cycle aimed at gaining insights from the 4-H Programme teachers which informed 2 lesson plans for cycles 2 and 3 respectively. I generated data through focus group interviews, observations, document analysis, video and tape recording, and my research journal entries. The data indicated the value of school food gardens in meeting curriculum requirements, particularly in relation to learner centred ideologies and the first principle of the national curriculum. As both researcher and mediator of learning, I developed skills and knowledge that helped me to understand working in the Foundation Phase. The study also revealed a need for meaningful integration within and across Learning Areas when planning lessons in the Life Skills Learning Programme. The study indicated that there is a need to develop assessment practices beyond a technical exercise to a more interpretive approach. Lastly this study offers some recommendations for further research into the use of school food gardens through taking the context of learners into account and by encouraging school community relationships that will also contribute in poverty alleviation.
Keywords: School gardens -- South Africa -- Eastern Cape; Gardening -- Study and teaching (Elementary) -- South Africa -- Eastern Cape; Environmental education -- Study and teaching (Elementary) -- South Africa --Eastern Cape; Environmental education -- South Africa -- Eastern Cape -- Case studies